EFEKTIVITAS PEMBELAJARAN AUDIOVISUAL TERHADAP TEKNIK DASAR PERMAINAN FUTSAL DI SEKOLAH : SYSTEMATIC LITERATURE REVIEW - Fathurrohman, Muhammad Andi; Subroto, Toto; Rahmat, Alit (Jurnal Porkes, 2024)
This research aims to find out how effective audiovisual learning is on the basic techniques of playing futsal in schools. This research was conducted using the Systematic Literature Review (SLR) method. This research uses the Harzing's Publish or Perish application with the database used to search for available literature, namely Google Scholar. The search for articles in this research was limited to the publication period of the last 5 years published in national open access journals. The prism flow diagram is used to identify articles through the data extraction filtering process. Of the 75 articles downloaded, the remaining 4 articles went through the inclusion and exclusion screening process using criteria and were analyzed. This research focuses on audiovisual learning of the basic techniques of playing futsal ball in schools. The results of the data identification show that audiovisual learning of the basic techniques of playing futsal in schools is very effective in terms of learning outcomes both in terms of motor development, motivation to learn and also coordination of basic techniques in playing futsal.